(untitled) (Bangladesh Journal of Medical Science, 2012)
Objective: The aim of the study was to analyse and compare statistically the incidence of accidental fall of instruments during elective and emergency caesarean section. Material and Methods: A prospective study was carried out at (V. C. S. G. G. Medical Sciences and Research Institute) Srinagar, Pauri Garhwal, India over a period of 24 months. The instrument fall during elective and emergency caesarean sections was observed. The observer counted the number of times an instrument fell during surgery. The personnel responsible were identified. A note of the nature of instrument falling was made. Results: We observed 362 surgeries which included 242 emergency caesarean sections and 120 elective caesarean sections. There were a total of 159 falls. Falls were classified as major and minor. There were 22 falls (18.33%) during elective caesarean sections and 137 falls (56.61%) during emergency caesarean sections. There were 53 major and 106 minor falls. Two or more falls were noted in 31 surgeries. In 96 instances (60.37%) the operating surgeon was responsible for the fall. In 37 cases (23.27%) assisting surgeon and in 17 cases (10.69%) the scrub nurse was responsible for the fall of the instruments. Nine falls (5.66%) were unaccountable. Most falls in elective caesarean section were in later half of the surgery while in emergency caesarean section, they were before and during the extraction of the baby. The surgeries were delayed, on an average by 5.7 minutes after a major fall of an instrument. Conclusions: Falling of instruments in the theatre is a common problem all over the world. This leads to increase in operating time, more resources and quality compromise. The operating surgeon was mainly responsible for the fall. Ashort training programme in instrument handling should be conducted for operating surgeons which may be helpful in preventing such avoidable falls. DOI: http://dx.doi.org/10.3329/bjms.v11i2.8957 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 87-90